(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
The research dealt with solving the transportation problem using the methods of the initial distribution (the northwest corner method, the method of least costs, the approximate Vogel method). Vogel’s approximate method is always considered the best way to solve transportation problems because it is the closest to the initial solution to the transportation problem, and it is the lowest possible cost to import food commodities from their sources (the three countries) to the country of consumption (Libya). And the final solution to the transportation problem was obtained by the modified distribution method, as this method confirmed that this cost, which was obtained using the approximate Vogel method, is the lowest possible cost among the other solutions. The final distribution table for the quantities of grain and the costs of each of the three exporting countries was also discussed, in addition to some conclusions and recommendations.